Fostering Future Investors: Analysing Determinants of Stock Market Participation Among Malaysian Students using PLS-SEM - Abdul Manaf, Suhaily Maizan; Amron, Mohd Talmizie; Abdullah, Zalinawati; Mohamad, Zuraida; Md Hashim, Sahaida Laily (Information Management and Business Review, 2024)
Participation in the stock market is crucial for financial engagement and wealth creation. However, specific population segments, such as students from higher learning institutions, may exhibit lower stock market participation levels. Addressing this issue, this study uses the behavioral finance theory to examine how financial literacy, financial well-being, herding behavior, overconfidence bias, risk tolerance, social interaction, and investment intention influence stock market participation. Data was collected through a self-administered questionnaire distributed to 669 university students in Malaysia aged 17-30 years old. The findings reveal that financial literacy, herding behavior, risk tolerance, and social interaction positively influenced investment intention. The study also discovered that investment intention positively influences stock market participation. This study has made significant contributions to both theory and practice. Theoretically, this study contributes to the literature by confirming the positive relationship between financial literacy and investment intention. This study contributes to the development of more effective interventions and policies that not only educate students about an essential aspect of financial literacy but also prepare them for a financially secure future.